2015
DOI: 10.3892/mmr.2015.3323
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer stem-like cells elicit the polarization of M2 macrophages

Abstract: Ovarian cancer is a life‑threatening disease in females worldwide. The polarization of macrophages is crucial in oncogenesis and the development of ovarian cancer. Increasing evidence has supported the correlation between ovarian cancer stem‑like cells (OCSCs) and macrophages, however, whether OCSCs can affect the polarization of macrophages and the underlying mechanisms involved remain to be elucidated. To examine the interplay between OCSCs and macrophages, a co‑culture system was used to detect the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…The impact of stromal cell components on the tumor microenvironment was described in several studies (Bezdenezhnykh et al , ; Wan et al , ; Zhang, Cai & Li, ). It is known that since the molecular composition of the microenvironment of the tumor is formed not only by cancer cells and CSCs and their metabolic products, but also by resident/infiltrating non‐tumor cells, inter‐ and intracellular interactions may be difficult to recapitulate in in vitro conditions.…”
Section: Modifying Three‐dimensional Cancer Stem Cell Modelsmentioning
confidence: 98%
“…The impact of stromal cell components on the tumor microenvironment was described in several studies (Bezdenezhnykh et al , ; Wan et al , ; Zhang, Cai & Li, ). It is known that since the molecular composition of the microenvironment of the tumor is formed not only by cancer cells and CSCs and their metabolic products, but also by resident/infiltrating non‐tumor cells, inter‐ and intracellular interactions may be difficult to recapitulate in in vitro conditions.…”
Section: Modifying Three‐dimensional Cancer Stem Cell Modelsmentioning
confidence: 98%
“…Various studies have indicated that inhibition of NF-κB activation helps to drive the tumor-promoting phenotype of TAMs [12, 13]. Macrophages are polarized to M2-like phenotype by malignant epithelial cells [14]. Positive correlation was found between macrophage infiltrated in the tumor stroma and OSCC with a higher histological grading [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, ovarian cancer or stem-like cancer cells were previously reported to polarize macrophages into M2 phenotype. [58][59][60] Therefore, we suggest that ovarian cancer cells tend to induce M2-like mRNA profile independent of their platinum sensitivity status. However, we examined only one ovarian cancer cell line and its derivatives, hence avoiding the possible impact of variation between different cell lines.…”
Section: Mechanisms Of Drug Cross-resistance In A2780-derived Cell Linesmentioning
confidence: 79%